PENCEMARAN PERAIRAN AKIBAT KADAR AMONIAK YANG TINGGI DARI LIMBAH CAIR INDUSTRI TEMPE - Harahap, Sampe (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
A research aims to understand the effectiveness of the use of palm (Elaisguineensis) shell as biofilter media in the aerobic system to decrease the ammonialevel in the tempe industry liquid waste has been conducted in the Tuah Karya Village,Pekanbaru. Results shown that during the seeding period, the value of ammonia was23.37-39.12 mg/L in the inlet. During the research period, the ammonia value was19.78-27.63 mg/L and by using the palm shell, the value was 25.52-39.48 mg/L in theinlet and 18.85-30.64 mg/L in the outlet. Without using the palm shell, the ammoniavalue was around 33.12-41.35 mg/L in the inlet and 28.17-34.69 mg/L in the outlet.Based on the results obtained, it can be concluded that the used of palm shell iseffecient to decrease the ammonia level in the tempe industry liquid waste.